KEAMANAN PANGAN KANTIN SEKOLAH BERDASARKAN SKOR KEAMANAN PANGAN ( SKP ) DI DESA PENYARINGAN, KECAMATAN MENDOYO - Ni Putu Wini Diah Pradnyani; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Food delivery is an activity of providing diverse food and meeting the safety, quality and nutrition requirements for public consumption. School canteen is a place of school where all school residents can buy snacks, both in the form of ready meals and processed foods. The purpose of this study was to determine the School Canteen Food Safety Based on the Food Safety Score (SKP) in Penyaringan Village, Mendoyo District, Jembrana Regency. Food safety is an effort to prevent the possibility of biological, chemical and other contaminants, which disturb, harm and endanger human health. Food safety score (SKP) is a score or value that illustrates the feasibility of food for consumption. The research variable is the Food Safety Score (SKP) which consists of 4 components, namely the Selection and Storage of Food Materials (PPB), Cooking Hygiene (HGP), Food Processing (PBM), Food Distribution (DPM). This study was an observational study with a cross-sectional approach in a school canteen in Penyaringan Village, Mendoyo District, Jembrana District in November 2019. The population in this study was elementary, junior and senior high school canteens in the Penyaringan Village area, Mendoyo District, Jembrana Regency amounts to 13 Canteens. Respondent identity data obtained through interviews using the form of identity and food safety score is done by direct observation using the food safety score assessment form. Data were analyzed descriptively from food safety scores (SKP). Based on the results of the interpretation of the Food Safety Score (SKP) it can be seen that as many as 30.8% school canteens are included in the medium category with the results of the interpretation of the Food Safety Score (SKP) values of 93.43% - 95.57% and  69.20% the school canteen is included in the vulnerable category, but it is safe to consume with its interpretation of the Food Safety Score (SKP) of 77.37% - 86.29%. To maintain the quality and cleanliness of food in the school canteen, canteen guards should always maintain hygiene and occupational health. The most characteristics of canteen guards in the age group of 46 - 55 years is 50%, while the most selling time is 11-20 years, namely 55.6%. The average food safety score (SKP) obtained is 0.8525 (85.25%). Included in the category of food safety are vulnerable, but safe for consumption.Keywords: school canteen, hygiene, and food safety score (SKP)